Preparation method and application of modified silicate flame retardant
By using montmorillonite modified with nitrogen, phosphorus, silicon biquaternary ammonium salt intercalator in the polymer, the problems of poor dispersion of inorganic silicate flame retardant in the polymer and the adverse effects on material properties are solved, and the problem of poor dispersion of inorganic silicate flame retardant in the polymer is achieved. Efficient flame retardant and mechanical properties improve.
Patent Information
- Application Number
- CN202411177415.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-26
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2044-08-26
AI Technical Summary
The existing inorganic silicate flame retardants have poor dispersion in polymer matrix and large amounts of addition, which has a serious impact on the mechanical and electrical properties of the material. They often use halogen-based flame retardants to produce toxic fumes when burned.
By synthesizing a nitrogen-phosphorus silicon biquaternary ammonium intercalation agent and montmorillonite, a modified silicate flame retardant is prepared and melt blended with polyethylene to form a nanocomposite material to improve flame retardant performance.
The organicization of layered silicates and better dispersion in polymers are achieved, the flame retardant and mechanical properties are enhanced, while the adverse effects on material properties are reduced, and the results are achieved at relatively low addition amounts. Good flame retardant modification effect.
Smart Images

Figure QLYQS_1 
Figure BDA0005011087810000031 
Figure BDA0005011087810000032
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of flame retardants, and in particular to a preparation method and application of a modified silicate flame retardant. Background Art
[0002] With the rise and development of nanomaterials and people's increasing environmental awareness, nano flame retardant systems have opened up new paths for the development of flame retardant polymers. Polymer materials such as plastics, rubbers and fibers are widely used in daily life. The obvious disadvantages of these materials are that they are flammable or combustible, and they produce a lot of smoke and harmful gases when burned, which has a serious impact on people's daily lives. Therefore, the flame retardancy of polymer materials is extremely important. Commonly used halogen flame retardants decompose a large amount of toxic smoke during combustion, which can easily cause poisoning and suffocation of people on the scene and affect vision and escape. Hydroxides combine the triple functions of flame retardancy, smoke suppression and filling. They are non-toxic and non-corrosive when burned. The raw materials are easy to obtain and inexpensive, but due to their large addition amount, they have a serious impact on the mechanical and electrical properties of polymers. Therefore, it is of great significance to research and develop new flame retardants that meet fire safety and environmental protection requirements and have little effect on the mechanical and electrical properties of materials.
[0003] Silicate minerals are aggregates of sheet silicate minerals, composed of silicon oxygen tetrahedrons and aluminum (magnesium) oxygen octahedron units. The tetrahedral sheets and octahedral sheets are superimposed in different forms through common oxygen atoms to form layered sheets, and there are interacting van der Waals forces between the sheets. This type of silicate mainly includes natural and synthetic silicates, and the most commonly used in the field of flame retardant research are montmorillonite, kaolin, sepiolite, hydrotalcite, etc.; however, layered silicates such as montmorillonite, if used alone, still have no significant flame retardant effect, mainly because the flame retardant mechanism of layered silicates is a barrier effect, that is, layered silicates block the transfer and diffusion of external heat and oxygen to the inside of the polymer matrix, and also block the release of internal combustible volatiles to the gas phase combustion zone, but the flame retardant effect is relatively single; therefore, it is necessary to overcome the shortcomings of layered silicates and diversify their flame retardant mechanism, which is a problem that needs to be solved urgently.
[0004] Chinese patent CN103788407B discloses a method for preparing a porous pillared layered silicate flame retardant, including the preparation of phosphorus-containing organic layered silicate, the preparation of phosphorus-nitrogen-containing organic layered silicate, the preparation of phosphorus-nitrogen silicon pillared layered silicate, and the preparation of phosphorus-nitrogen-silicon pillared porous silicate flame retardant. However, the flame retardant prepared by the patent needs to be roasted at high temperature, and there is no organic substance on the surface, and the compatibility with organic polymers is poor. If organic polymers are added, the physical and mechanical properties of the polymer will be damaged to a certain extent; the present invention synthesizes a novel nitrogen-phosphorus-silicon type quaternary ammonium salt as an intumescent flame retardant and an intercalation agent modified silicate, and prepares an organic nitrogen-phosphorus-silicon system-montmorillonite flame retardant by ion exchange reaction, and then melt-blended with polyethylene, not only realizing the organicization of the layered silicate surface, but also facilitating its dispersion in polymer materials, and making the layered silicate and the organic flame retardant better play a synergistic effect, which is conducive to the improvement of the flame retardant properties of polyethylene materials. Summary of the invention
[0005] The purpose of the present invention is to overcome the shortcomings of the prior art, provide a preparation method and application of a modified silicate flame retardant, overcome the problems of large addition amount of conventional inorganic silicate flame retardants and poor dispersion in polymer matrix, and provide an intumescent heat-resistant silicate flame retardant integrating enhancement, flame retardancy and smoke suppression functions.
[0006] To achieve the above object, the technical solution adopted by the present invention is:
[0007] A method for preparing a modified silicate flame retardant comprises the following steps: weighing an inorganic silicate and dissolving it in deionized water, ultrasonically dispersing it at 70-85°C for 20-40 minutes, and after the dispersion is uniform, adding a The nitrogen-phosphorus-silicon diquaternary ammonium salt intercalant is stirred for 16-24 hours, filtered while hot, washed with deionized water, and the filtrate is tested for precipitation with silver nitrate. After drying, a modified silicate flame retardant is obtained.
[0008] The ratio of inorganic silicate to nitrogen-phosphorus-silicon diquaternary ammonium salt intercalation agent is 100g:(30-50)g.
[0009] The inorganic silicate is montmorillonite.
[0010] Furthermore, the preparation method of the nitrogen-phosphorus-silicon diquaternary ammonium salt intercalation agent comprises the following steps:
[0011] Step (1), under a nitrogen atmosphere, add tris(hydroxymethyl)aminomethane and 1,4-dioxane to a reaction flask, stir evenly, add triethylamine and chloromethyltrichlorosilane, stir to react, filter while hot after the reaction is complete, dissolve the filtered solid with deionized water, add sodium hydroxide aqueous solution to adjust the pH to 7-8, filter again, wash and dry to obtain chloromethylmethylamine silicon-containing cage ester. The preparation reaction formula is as follows:
[0012]
[0013] Step (2), under nitrogen atmosphere, add 2-[(6-oxy-6H-diphenyl[c,e][1,2]oxaphosphorinane-6-yl)methyl]succinic acid and tetrahydrofuran to the reaction flask, stir evenly, add 2-chloro-1-methylpyridinium iodide and triethylamine, react at 45-60° C. for 3-8 hours, add ethyl acetate and deionized water for extraction, concentrate the organic phase, and purify by column chromatography to obtain chloromethyl nitrogen phosphorus silicon intermediate. The preparation reaction formula is as follows:
[0014]
[0015] Step (3), under nitrogen atmosphere, add chloromethyl nitrogen phosphorus silicon intermediate and N, N-dimethylformamide to the reaction flask, stir evenly, add long-chain alkyl dimethyl tertiary amine, react at 80-100° C. for 12-24 hours, cool to room temperature, recrystallize with acetone, filter, wash with deionized water, and dry to obtain nitrogen phosphorus silicon diquaternary ammonium salt intercalation agent. The preparation reaction formula is as follows:
[0016]
[0017] Furthermore, the mass fraction of the sodium hydroxide aqueous solution in step (1) is 15-30%.
[0018] Furthermore, in step (1), the ratio of tris(hydroxymethyl)aminomethane, triethylamine and chloromethyltrichlorosilane is 1 mol:(1.5-2) mol:(1.05-1.2) mol.
[0019] Furthermore, in step (1), the reaction temperature is 65-80° C. and the reaction time is 5-12 h.
[0020] Furthermore, in step (2), the ratio of 2-[(6-oxy-6H-diphenyl[c,e][1,2]oxaphosphorinane-6-yl)methyl]butanedioic acid, 2-chloro-1-methylpyridinium iodide and triethylamine is 1 mol:(2.5-3.5) mol:(4-6) mol.
[0021] Furthermore, in step (3), the long-chain alkyl dimethyl tertiary amine is any one of dodecyl dimethyl tertiary amine, hexadecyl dimethyl tertiary amine or octadecyl dimethyl tertiary amine.
[0022] Furthermore, in step (3), the ratio of the chloromethyl nitrogen phosphorus silicon intermediate to the long-chain alkyl dimethyl tertiary amine is 1 mol: (2.1-2.3) mol.
[0023] Furthermore, 5-25 parts by weight of modified silicate flame retardant are added to 100 parts by weight of polyethylene, mixed evenly, placed on a double-roll mixer for melt mixing at 140-155°C, and after mixing evenly, molded in a flat vulcanizer at 160-175°C for 5-10 minutes to obtain flame-retardant polyethylene.
[0024] Furthermore, the rotation speed of the twin-roll mixer is 20-30 r / min, and the mixing time is 25-40 min.
[0025] By adopting the above technical solution, the beneficial effects of the present invention are:
[0026] The invention uses trishydroxymethylaminomethane, chloromethyltrichlorosilane, 2-[(6-oxy-6H-diphenyl[c,e][1,2]oxaphosphorinane-6-yl)methyl]succinic acid and long-chain alkyl dimethyl tertiary amine as raw materials to prepare and synthesize a nitrogen-phosphorus-silicon diquaternary ammonium salt intercalation agent, and generates an intercalation reaction with montmorillonite through an ion exchange reaction to obtain a modified silicate flame retardant, and finally melt-blended with polyethylene to obtain flame-retardant polyethylene.
[0027] The nitrogen-phosphorus-silicon diquaternary ammonium salt intercalant contains a diquaternary ammonium salt structure, in which one ion reacts with the exchangeable ions of the montmorillonite layer, and the other ion also produces an exchange ion reaction in the same layer, replacing the sodium ions in the montmorillonite to achieve ion exchange, thereby entering the interlayer of the montmorillonite, so that the montmorillonite layer is stretched, the interlayer distance is expanded, and the surface energy of the layer is reduced, the affinity between the macromolecular chain and the silicate is improved, and better dispersibility is formed, thereby effectively reducing the particle size of the flame retardant; the organic cations in the nitrogen-phosphorus-silicon diquaternary ammonium salt intercalant can play a pre-swelling role on the interlayer distance of the montmorillonite, thereby reducing the agglomeration tendency of the montmorillonite, so that it is easier to obtain montmorillonite particles with smaller particle size and more uniform distribution, which is conducive to the insertion of the polymer chain into the montmorillonite interlayer to form a nano-composite material.
[0028] The nitrogen-phosphorus-silicon diquaternary ammonium salt intercalant improves the dispersion of montmorillonite in a polyethylene matrix, forms an exfoliation layer, and plays an effective barrier role in the polymer combustion process. The nitrogen-phosphorus-silicon structure itself also has an expansion flame retardant effect. After burning in the air, the expansion flame retardant loaded on the surface of the montmorillonite breaks the phosphate bond and catalyzes carbonization and releases non-flammable gas, and forms an expanded and dense carbon layer together with the montmorillonite layer. The dual flame retardant effect enables it to achieve a better flame retardant modification effect at a relatively low addition amount; improves the dispersibility and compatibility of montmorillonite in a polyethylene matrix, and promotes the enhancement and modification effect of montmorillonite on polyethylene; the modified silicate flame retardant prepared by the invention can also be directly applied to other polymer processing processes, with low production cost and easy implementation. DETAILED DESCRIPTION
[0029] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0030] Tris(hydroxymethyl)aminomethane, CAS number is 77-86-1.
[0031] Chloromethyltrichlorosilane, CAS number is 1558-25-4.
[0032] 2-[(6-oxy-6H-dibenzo[c,e][1,2]oxaphosphorinane-6-yl)methyl]butanedioic acid (flame retardant DDP), CAS number is 63562-33-4.
[0033] 2-Chloro-1-methylpyridinium iodide (CMPI), CAS number 14338-32-0.
[0034] Dodecyl dimethyl tertiary amine, CAS number is 112-18-5.
[0035] Hexadecyl dimethyl tertiary amine, CAS number is 112-69-6.
[0036] Octadecyl dimethyl tertiary amine, CAS number is 124-28-7.
[0037] Example 1
[0038] (1) Under a nitrogen atmosphere, 32 mmol of tris(hydroxymethyl)aminomethane and 228 mL of 1,4-dioxane were added to a reaction flask, and after stirring, 56 mol of triethylamine and 36.8 mmol of chloromethyltrichlorosilane were added, and the mixture was reacted at 75° C. for 8 h. The mixture was filtered while hot, and the filtered solid was dissolved in deionized water. A 25% by mass sodium hydroxide aqueous solution was added to adjust the pH to 8, and the mixture was filtered again, washed, and dried to obtain a chloromethylmethylamine silicon-containing cage ester.
[0039] (2) Under nitrogen atmosphere, 30 mmol of 2-[(6-oxy-6H-diphenyl[c,e][1,2]oxaphosphorinane-6-yl)methyl]butanedioic acid and 405 mL of tetrahydrofuran were added to the reaction flask, and after stirring, 90 mmol of 2-chloro-1-methylpyridinium iodide and 150 mmol of triethylamine were added, and the mixture was reacted at 55° C. for 5 h. Ethyl acetate and deionized water were added for extraction, and the organic phase was concentrated and purified by column chromatography. The mobile phase was ethyl acetate and petroleum ether in a ratio of 1:3 to obtain a chloromethyl nitrogen phosphorus silicon intermediate.
[0040] (3) Under nitrogen atmosphere, 25 mmol of chloromethyl nitrogen phosphosilicon intermediate and 650 mL of N,N-dimethylformamide were added to the reaction flask, and after stirring, 55 mmol of dodecyl dimethyl tertiary amine was added, and the mixture was reacted at 90° C. for 16 h. The mixture was cooled to room temperature, recrystallized from acetone, filtered, washed with deionized water, and dried to obtain the nitrogen phosphosilicon diquaternary ammonium salt intercalation agent.
[0041] (4) Weigh 100 g of montmorillonite and dissolve it in deionized water. Ultrasonic dispersion is performed at 75° C. for 30 min. After uniform dispersion, 30 g of nitrogen-phosphorus-silicon diquaternary ammonium salt intercalant is added. Stirring is continued for 18 h. The mixture is filtered while hot and washed with deionized water. The filtrate is tested for precipitation with silver nitrate. The modified silicate flame retardant is obtained after drying.
[0042] Example 2
[0043] (1) Under a nitrogen atmosphere, 80 mmol of tris(hydroxymethyl)aminomethane and 400 mL of 1,4-dioxane were added to a reaction flask, and after stirring, 120 mmol of triethylamine and 84 mmol of chloromethyltrichlorosilane were added, and the mixture was reacted at 80° C. for 5 h. The mixture was filtered while hot, and the filtered solid was dissolved in deionized water. A 15% by mass sodium hydroxide aqueous solution was added to adjust the pH to 7, and the mixture was filtered again, washed, and dried to obtain a chloromethylmethylamine silicon-containing cage ester.
[0044] (2) Under nitrogen atmosphere, 75 mmol of 2-[(6-oxy-6H-diphenyl[c,e][1,2]oxaphosphorinane-6-yl)methyl]butanedioic acid and 900 mL of tetrahydrofuran were added to the reaction flask, and after stirring, 187.5 mmol of 2-chloro-1-methylpyridinium iodide and 300 mmol of triethylamine were added, and the mixture was reacted at 60° C. for 3 h. Ethyl acetate and deionized water were added for extraction, and the organic phase was concentrated and purified by column chromatography. The mobile phase was ethyl acetate and petroleum ether in a ratio of 1:3 to obtain a chloromethyl nitrogen phosphorus silicon intermediate.
[0045] (3) Under nitrogen atmosphere, 70 mmol of chloromethyl nitrogen phosphosilicon intermediate and 1400 mL of N,N-dimethylformamide were added to the reaction flask, and after stirring, 147 mmol of hexadecyl dimethyl tertiary amine was added, and the mixture was reacted at 100° C. for 12 h. The mixture was cooled to room temperature, recrystallized from acetone, filtered, washed with deionized water, and dried to obtain a nitrogen phosphosilicon diquaternary ammonium salt intercalation agent.
[0046] (4) Weigh 100 g of montmorillonite and dissolve it in deionized water. Ultrasonic dispersion is performed at 85° C. for 20 min. After uniform dispersion, 35 g of nitrogen-phosphorus-silicon diquaternary ammonium salt intercalant is added. Stirring is continued for 24 h. The mixture is filtered while hot and washed with deionized water. The filtrate is tested for precipitation with silver nitrate. The modified silicate flame retardant is obtained after drying.
[0047] Example 3
[0048] (1) Under a nitrogen atmosphere, 30 mmol of tris(hydroxymethyl)aminomethane and 300 mL of 1,4-dioxane were added to a reaction flask, and after stirring, 60 mmol of triethylamine and 36 mmol of chloromethyltrichlorosilane were added, and the mixture was reacted at 65° C. for 12 h. The mixture was filtered while hot, and the filtered solid was dissolved in deionized water. A 30% by mass sodium hydroxide aqueous solution was added to adjust the pH to 8, and the mixture was filtered again, washed, and dried to obtain a chloromethylmethylamine silicon-containing cage ester.
[0049] (2) Under nitrogen atmosphere, 26 mmol of 2-[(6-oxy-6H-diphenyl[c,e][1,2]oxaphosphorinane-6-yl)methyl]butanedioic acid and 390 mL of tetrahydrofuran were added to the reaction flask. After stirring evenly, 91 mmol of 2-chloro-1-methylpyridinium iodide and 156 mmol of triethylamine were added. The mixture was reacted at 45° C. for 8 h. Ethyl acetate and deionized water were added for extraction. The organic phase was concentrated and purified by column chromatography. The mobile phase was ethyl acetate and petroleum ether in a ratio of 1:3 to obtain a chloromethyl nitrogen phosphorus silicon intermediate.
[0050] (3) Under nitrogen atmosphere, 22 mmol of chloromethyl nitrogen phosphosilicon intermediate and 660 mL of N,N-dimethylformamide were added to the reaction flask, and after stirring, 50.6 mmol of octadecyl dimethyl tertiary amine was added, and the mixture was reacted at 80° C. for 24 h. The mixture was cooled to room temperature, recrystallized from acetone, filtered, washed with deionized water, and dried to obtain the nitrogen phosphosilicon diquaternary ammonium salt intercalation agent.
[0051] (4) Weigh 100 g of montmorillonite and dissolve it in deionized water. Ultrasonic dispersion is performed at 70° C. for 40 min. After uniform dispersion, 40 g of nitrogen-phosphorus-silicon diquaternary ammonium salt intercalant is added. Stirring is continued for 24 h. The mixture is filtered while hot and washed with deionized water. The filtrate is tested for precipitation with silver nitrate. The modified silicate flame retardant is obtained after drying.
[0052] Example 4
[0053] (1) Under a nitrogen atmosphere, 42 mmol of tris(hydroxymethyl)aminomethane and 355 mL of 1,4-dioxane were added to a reaction flask, and after stirring, 69.3 mmol of triethylamine and 48.2 mmol of chloromethyltrichlorosilane were added, and the mixture was reacted at 70° C. for 9 h. The mixture was filtered while hot, and the filtered solid was dissolved in deionized water. A 20% by mass sodium hydroxide aqueous solution was added to adjust the pH to 8, and the mixture was filtered again, washed, and dried to obtain a chloromethylmethylamine silicon-containing cage ester.
[0054] (2) Under nitrogen atmosphere, 36 mmol of 2-[(6-oxy-6H-diphenyl[c,e][1,2]oxaphosphorinane-6-yl)methyl]butanedioic acid and 485 mL of tetrahydrofuran were added to the reaction flask. After stirring, 102.6 mmol of 2-chloro-1-methylpyridinium iodide and 162 mmol of triethylamine were added. The mixture was reacted at 55° C. for 7 h. Ethyl acetate and deionized water were added for extraction. The organic phase was concentrated and purified by column chromatography. The mobile phase was ethyl acetate and petroleum ether in a ratio of 1:3 to obtain a chloromethyl nitrogen phosphorus silicon intermediate.
[0055] (3) Under nitrogen atmosphere, 28 mmol of chloromethyl nitrogen phosphosilicon intermediate and 720 mL of N,N-dimethylformamide were added to the reaction flask, and after stirring, 63 mmol of dodecyl dimethyl tertiary amine was added, and the mixture was reacted at 95 °C for 15 h. The mixture was cooled to room temperature, recrystallized from acetone, filtered, washed with deionized water, and dried to obtain the nitrogen phosphosilicon diquaternary ammonium salt intercalation agent.
[0056] (4) Weigh 100 g of montmorillonite and dissolve it in deionized water. Ultrasonic dispersion is performed at 85° C. for 30 min. After uniform dispersion, 45 g of nitrogen-phosphorus-silicon diquaternary ammonium salt intercalant is added. Stirring is continued for 20 h. Filter while hot, wash with deionized water, and detect the filtrate with silver nitrate to find out that there is no precipitation. After drying, a modified silicate flame retardant is obtained.
[0057] Example 5
[0058] (1) Under a nitrogen atmosphere, 20 mmol of tris(hydroxymethyl)aminomethane and 180 mL of 1,4-dioxane were added to a reaction flask, and after stirring, 35 mmol of triethylamine and 23 mmol of chloromethyltrichlorosilane were added, and the mixture was reacted at 75° C. for 8 h. The mixture was filtered while hot, and the filtered solid was dissolved in deionized water. A 25% by mass sodium hydroxide aqueous solution was added to adjust the pH to 8, and the mixture was filtered again, washed, and dried to obtain a chloromethylmethylamine silicon-containing cage ester.
[0059] (2) Under nitrogen atmosphere, 16 mmol of 2-[(6-oxy-6H-diphenyl[c,e][1,2]oxaphosphorinane-6-yl)methyl]butanedioic acid and 240 mL of tetrahydrofuran were added to the reaction flask, and after stirring, 45.6 mmol of 2-chloro-1-methylpyridinium iodide and 88 mmol of triethylamine were added, and the mixture was reacted at 50° C. for 4 h. Ethyl acetate and deionized water were added for extraction, and the organic phase was concentrated and purified by column chromatography. The mobile phase was ethyl acetate and petroleum ether in a ratio of 1:3 to obtain a chloromethyl nitrogen phosphorus silicon intermediate.
[0060] (3) Under nitrogen atmosphere, 12 mmol of chloromethyl nitrogen phosphosilicon intermediate and 282 mL of N,N-dimethylformamide were added to the reaction flask, and after stirring, 27 mmol of hexadecyl dimethyl tertiary amine was added, and the mixture was reacted at 95 °C for 15 h. The mixture was cooled to room temperature, recrystallized from acetone, filtered, washed with deionized water, and dried to obtain the nitrogen phosphosilicon diquaternary ammonium salt intercalation agent.
[0061] (4) Weigh 100 g of montmorillonite and dissolve it in deionized water. Ultrasonic dispersion is performed at 80° C. for 35 min. After uniform dispersion, 50 g of nitrogen-phosphorus-silicon diquaternary ammonium salt intercalant is added. Stirring is continued for 24 h. The mixture is filtered while hot and washed with deionized water. The filtrate is tested for precipitation with silver nitrate. The modified silicate flame retardant is obtained after drying.
[0062] Comparative Example 1
[0063] Weigh 100g of montmorillonite and dissolve it in deionized water. Ultrasonic dispersion is carried out at 75℃ for 30min. After uniform dispersion, 30g of dodecyltrimethylammonium chloride (structural formula: The CAS number is 112-00-5), stirring is continued for 18 hours, filtered while hot, washed with deionized water, the filtrate is tested with silver nitrate to determine if there is no precipitation, and dried to obtain a silicate flame retardant.
[0064] Comparative Example 2
[0065] Weigh 100 g of montmorillonite and dissolve it in deionized water. Perform ultrasonic dispersion at 75° C. for 30 minutes. After uniform dispersion, filter while hot, wash with deionized water, detect the filtrate with silver nitrate to ensure that there is no precipitation, and obtain a silicate flame retardant after drying.
[0066] Interlayer spacing test: According to the method reported in "Theory and Practice of Polymer / Layered Silicate Nanocomposites" (Qi Zongneng, Shang Wenyu, Chemical Industry Press, 2002), the interlayer spacing of modified silicate flame retardant particles was tested by X-ray diffractometer. The step scanning method was adopted, with a step length of 0.01, a scanning range of 1-10°, and a scanning speed of 2° / min. The interlayer spacing was calculated according to the Bragg equation.
[0067] Average particle size test: According to the method reported in "Theory and Practice of Polymer / Layered Silicate Nanocomposites" (Qi Zongneng, Shang Wenyu, Chemical Industry Press, 2002), a small amount of modified silicate flame retardant particles were uniformly dispersed in ethanol, a small amount of liquid was dipped into a copper mesh, the solvent was dried, and the particle size of the silicate flame retardant was observed using a transmission electron microscope, with an electron acceleration voltage of 200 kV. The test results are shown in Table 1.
[0068] Table 1 Performance test of silicate flame retardant
[0069] Interlayer spacing (nm) Average particle size (nm) Example 1 2.31 65.2 Example 2 3.54 51.3 Example 3 4.68 42.0 Example 4 6.15 35.6 Example 5 6.40 29.2 Comparative Example 1 1.59 73.1 Comparative Example 2 1.21 92.5
[0070] It can be seen from the test results in Table 2 that with the increase of the content of nitrogen-phosphorus-silicon diquaternary ammonium salt intercalation agent, the interlayer spacing of the modified silicate flame retardant gradually increases and the average particle size gradually decreases. This is because the nitrogen-phosphorus-silicon diquaternary ammonium salt intercalation agent contains a diquaternary ammonium salt structure. After one ion reacts with the exchangeable ions of the montmorillonite layer, the other ion also produces an exchange ion reaction in the same layer, replacing the sodium ions in the montmorillonite to achieve ion exchange, thereby entering the interlayer of the montmorillonite, causing the montmorillonite layer to open, expanding the interlayer spacing while reducing the surface energy of the layer, thereby increasing the affinity between the macromolecular chain and the silicate, forming a better dispersibility, and then effectively reducing the particle size of the flame retardant; the organic cations in the nitrogen-phosphorus-silicon diquaternary ammonium salt intercalation agent can play a pre-swelling role on the interlayer spacing of the montmorillonite, thereby reducing the agglomeration tendency of the montmorillonite, thereby making it easier to obtain montmorillonite particles with a smaller particle size and a more uniform distribution, which is conducive to the insertion of the polymer chain into the montmorillonite interlayer to form a nanocomposite material.
[0071] The intercalant in Comparative Example 1 is a common dodecyltrimethylammonium chloride structure, which has a limited chain length and fewer interaction sites with montmorillonite, and the intercalation effect is not obvious; in Comparative Example 2, no intercalant was added, and the charge repulsion effect between the layers was large, resulting in a small interlayer spacing and poor compatibility with the polymer matrix.
[0072] Example 6
[0073] 5 g of modified silicate flame retardant (prepared in Example 4) was added to 100 g of polyethylene, and after mixing evenly, it was placed on a double-roll mixer at a speed of 25 r / min and melt-kneaded at 145°C for 30 min. After mixing evenly, it was molded in a flat vulcanizer at 165°C for 8 min to obtain flame-retardant polyethylene.
[0074] Example 7
[0075] 10 g of modified silicate flame retardant (prepared in Example 4) was added to 100 g of polyethylene, and after mixing evenly, it was placed on a double-roll mixer at a speed of 20 r / min and melt-kneaded at 155°C for 25 min. After mixing evenly, it was molded in a flat vulcanizer at 175°C for 5 min to obtain flame-retardant polyethylene.
[0076] Example 8
[0077] 15 g of modified silicate flame retardant (prepared in Example 4) was added to 100 g of polyethylene, and after mixing evenly, it was placed on a double-roll mixer at a speed of 30 r / min and melt-kneaded at 140°C for 40 min. After mixing evenly, it was molded in a flat vulcanizer at 160°C for 10 min to obtain flame-retardant polyethylene.
[0078] Example 9
[0079] Add 20 g of modified silicate flame retardant (prepared in Example 4) to 100 g of polyethylene, mix well, place on a double-roll mixer at a speed of 28 r / min at 150°C for melt mixing, the mixing time is 30 min, and after mixing well, mold in a flat vulcanizer at 170°C for 9 min to obtain flame-retardant polyethylene.
[0080] Example 10
[0081] 25 g of modified silicate flame retardant (prepared in Example 4) was added to 100 g of polyethylene, and after mixing evenly, it was placed on a double-roll mixer at a speed of 30 r / min and melt-kneaded at 150°C for 35 min. After mixing evenly, it was molded in a flat vulcanizer at 170°C for 6 min to obtain flame-retardant polyethylene.
[0082] Comparative Example 3
[0083] Add 5g of silicate flame retardant (prepared by Comparative Example 1) to 100g of polyethylene, mix well, place on a double-roll mixer with a rotation speed of 25r / min at 145°C for melt mixing, the mixing time is 30min, and after mixing well, mold in a flat vulcanizer at 165°C for 8min to obtain flame-retardant polyethylene.
[0084] Comparative Example 4
[0085] Add 5g of silicate flame retardant (prepared by Comparative Example 2) to 100g of polyethylene, mix well, place on a double-roll mixer with a rotation speed of 25r / min at 145°C for melt mixing, the mixing time is 30min, after mixing well, mold in a flat vulcanizer at 165°C for 8min to obtain flame-retardant polyethylene.
[0086] Comparative Example 5
[0087] 100 g of polyethylene was placed on a twin-roll mixer at a rotation speed of 25 r / min and melt-kneaded at 145° C. for 30 min. After uniform mixing, it was molded in a flat vulcanizer at 165° C. for 8 min to obtain polyethylene.
[0088] Flame retardant performance test: tested on a cone calorimeter with a thermal radiation power of 35kW / m 2 , sample size: 100mm×100mm×3mm, see Table 2.
[0089] Table 2 Flame retardant properties test of polyethylene
[0090]
[0091]
[0092] The lower the peak value of the heat release rate, the less heat the material releases when burning, which helps to reduce the severity and spread of the fire; from the test results in Table 2, it can be seen that with the increase in the content of the modified silicate flame retardant, the flame retardant properties of polyethylene gradually increase, and its heat release rate peak value, average heat release rate and total heat release are all lower than those of the comparative example, and the flame retardant properties are excellent. This is because the nitrogen-phosphorus-silicon diquaternary ammonium salt intercalant improves the dispersion of montmorillonite in the polyethylene matrix, and the formation of a peeling layer plays an effective barrier role in the polymer combustion process. The nitrogen-phosphorus-silicon structure itself also has an intumescent flame retardant effect. After burning in the air, the intumescent flame retardant loaded on the surface of the montmorillonite breaks the phosphate bond and catalyzes the carbonization and the release of incombustible gas, and forms an expanded and dense carbon layer together with the montmorillonite layer. The dual flame retardant effect enables it to achieve a better flame retardant modification effect at a relatively low addition amount; Comparative Example 5 is pure polyethylene and does not have flame retardant properties.
[0093] Mechanical properties test: Tested in accordance with the relevant provisions of GB / T 1040-79. See Table 3 for test results.
[0094] Table 3 Mechanical properties test of polyethylene
[0095]
[0096]
[0097] The addition of modified silicate flame retardants increases the mechanical properties of polyethylene materials to varying degrees. The tensile strength in Example 10 is 20.64 MPa and the elastic modulus is 213.42 MPa. This is because the nitrogen-phosphorus-silicon diquaternary ammonium salt intercalant improves the dispersibility and compatibility of montmorillonite in the polyethylene matrix, promoting the reinforcing and modifying effect of montmorillonite on polyethylene.
[0098] The above-mentioned embodiments only express several implementation methods of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the patent application. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present application, which all belong to the protection scope of the present application.
Claims
1. A method for preparing a modified silicate flame retardant, characterized in that: The preparation method comprises the following steps: weighing an inorganic silicate and dissolving it in deionized water, ultrasonically dispersing it at 70-85° C. for 20-40 minutes, and after the dispersion is uniform, adding a The nitrogen-phosphorus-silicon diquaternary ammonium salt intercalant is stirred for 16-24 hours, filtered while hot, washed with deionized water, and the filtrate is tested for precipitation with silver nitrate, and dried to obtain a modified silicate flame retardant; The ratio of the inorganic silicate to the nitrogen-phosphorus-silicon diquaternary ammonium salt intercalant is 100 g: (30-50) g; The inorganic silicate is montmorillonite.
2. The method for preparing the modified silicate flame retardant according to claim 1, characterized in that: The preparation method of the nitrogen-phosphorus-silicon diquaternary ammonium salt intercalation agent comprises the following steps: Step (1), under a nitrogen atmosphere, add tris(hydroxymethyl)aminomethane and 1,4-dioxane to a reaction flask, stir evenly, add triethylamine and chloromethyltrichlorosilane, stir to react, filter while hot after the reaction is complete, dissolve the filtered solid with deionized water, add sodium hydroxide aqueous solution to adjust the pH to 7-8, filter again, wash and dry to obtain chloromethylmethylamine silicon-containing cage ester; Step (2), under a nitrogen atmosphere, add chloromethyl methylamine silicon-containing cage ester, 2-[(6-oxy-6H-diphenyl[c,e][1,2]oxaphosphorinane-6-yl)methyl]succinic acid and tetrahydrofuran to a reaction flask, stir evenly, add 2-chloro-1-methylpyridinium iodide and triethylamine, react at 45-60° C. for 3-8 h, add ethyl acetate and deionized water for extraction, concentrate the organic phase, and purify by column chromatography to obtain a chloromethyl nitrogen phosphorus silicon intermediate; Step (3), under nitrogen atmosphere, add chloromethyl nitrogen phosphorus silicon intermediate and N, N-dimethylformamide into a reaction flask, stir evenly, add long-chain alkyl dimethyl tertiary amine, react at 80-100° C. for 12-24 hours, cool to room temperature, recrystallize from acetone, filter, wash with deionized water, and dry to obtain nitrogen phosphorus silicon diquaternary ammonium salt intercalation agent.
3. The method for preparing the modified silicate flame retardant according to claim 2, characterized in that: The mass fraction of the sodium hydroxide aqueous solution in step (1) is 15-30%.
4. The method for preparing the modified silicate flame retardant according to claim 2, characterized in that: In the step (1), the ratio of tris(hydroxymethyl)aminomethane, triethylamine and chloromethyltrichlorosilane is 1 mol: (1.5-2) mol: (1.05-1.2) mol.
5. The method for preparing the modified silicate flame retardant according to claim 2, characterized in that: In the step (1), the reaction temperature is 65-80° C. and the reaction time is 5-12 h.
6. The method for preparing the modified silicate flame retardant according to claim 2, characterized in that: In the step (2), the ratio of 2-[(6-oxy-6H-diphenyl[c,e][1,2]oxaphosphorinane-6-yl)methyl]butanedioic acid, 2-chloro-1-methylpyridinium iodide and triethylamine is 1 mol: (2.5-3.5) mol: (4-6) mol.
7. The method for preparing the modified silicate flame retardant according to claim 2, characterized in that: In the step (3), the long-chain alkyl dimethyl tertiary amine is any one of dodecyl dimethyl tertiary amine, hexadecyl dimethyl tertiary amine or octadecyl dimethyl tertiary amine.
8. The method for preparing the modified silicate flame retardant according to claim 2, characterized in that: In the step (3), the ratio of the chloromethyl nitrogen phosphorus silicon intermediate to the long-chain alkyl dimethyl tertiary amine is 1 mol: (2.1-2.3) mol.
9. Use of the modified silicate flame retardant obtained by the preparation method according to any one of claims 1 to 8 in flame retardant polyethylene, characterized in that: Add 5-25 parts by weight of modified silicate flame retardant to 100 parts by weight of polyethylene, mix well, place on a double-roll mixer at 140-155°C for melt mixing, and after mixing well, mold in a flat vulcanizer at 160-175°C for 5-10 minutes to obtain flame-retardant polyethylene.
10. The use of the modified silicate flame retardant in flame retardant polyethylene according to claim 9, characterized in that: The rotation speed of the twin-roll mixer is 20-30 r / min, and the mixing time is 25-40 min.
Citation Information
Patent Citations
A kind of preparation method of porous pillared layered silicate flame retardant
CN103788407B
Active organic silicon-nitrogen flame retardant compound and preparation method thereof
CN112011089A
DDP polyphosphate flame retardant and preparation method thereof
CN112225902A